Desenvolvimento de tarifas Time of use considerando o perfil de consumidores residenciais e comerciais utilizando pertinências Fuzzy e programação linear - Hammarstron, Júlia Rambo (2021)
Over the years, the behavior of electricity consumers has changed, especially with the introduction of a greater variety of electrical equipment into the market. This insertion of technologies results in a modification of the load curve imposed on the electrical system by increasing demand, with the need for greater electricity generation, investment in expansion, reinforcement and reconductoring of the electric power grid, in order to avoid overloading in the transmission and distribution lines. To postpone these investments, a demand side management (DSM) plan is used. One of these strategies is the application of differentiated rates throughout the day. These tariffs discourage consumption by increasing the energy tariff. This work aims to optimize the use of the electricity distribution system, through the increase of the load factor (LF), using a new Time of Use (ToU) tariff tool. The methodology evaluates the demand level of the load curves of groups of consumers and the Utility using Fuzzy pertinences, determining the most suitable prices for each group of consumers using Linear Programming. The validation of the methodology is performed based on data from a Utility located in the south of Brazil, considering its current fixed tariff. It was possible to determine a ToU tariff for each group of consumers, taking into account not only the consumption behavior patterns, but also the consumption behavior of all the Utility. It is possible to obtain gains with the application of these tariffs for the Utility, which optimizes its system, and for the consumers, with the reduction of electricity costs, depending if they are willing to change their consumption habits.